2018
DOI: 10.1155/2018/2767563
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Mechanical Properties and Reaction Characteristics of Al‐PTFE Composites with Different Al Particle Size

Abstract: Al-PTFE (aluminum-polytetrafluoroethylene) serves as one among the most promising reactive materials (RMs). In this work, six types of Al-PTFE composites with different Al particle sizes (i.e., 50 nm, 1∼2 μm, 6∼7 μm, 12∼14 μm, 22∼24 μm, and 32∼34 μm) were prepared, and quasistatic compression and drop weight tests were conducted to characterize the mechanical properties and reaction characteristics of Al-PTFE composites. e reaction phenomenon and stress-strain curves were recorded by a high-speed camera and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…Shen [2] used Taylor bar impact experiments to study the law of deformation and ignition time of PTFE/Ti energetic materials caused by the impact of the material ratio and the impact speed of the bar. Wu et al [3] used drop weight experiments to characterize the reaction characteristics of PTFE/Al and concluded that the characteristic drop height and ignition energy increase with the increase of Al particle size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shen [2] used Taylor bar impact experiments to study the law of deformation and ignition time of PTFE/Ti energetic materials caused by the impact of the material ratio and the impact speed of the bar. Wu et al [3] used drop weight experiments to characterize the reaction characteristics of PTFE/Al and concluded that the characteristic drop height and ignition energy increase with the increase of Al particle size.…”
Section: Introductionmentioning
confidence: 99%
“…McGregor et al [4] studied the impact response threshold of 40% density PTFE/Al energetic materials under impact. Dolgoborodov et al [5] found that porous PTFE/Al (0.4~0.5 g/cm 3 ) energetic materials can form stable detonation under the impact pressure of 1 GPa. By testing the reaction process of metal fluorocarbon-based reaction materials, Koch et al [6] concluded that the material's ability to react in metal fluorocarbon-based systems is significantly correlated with temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this nding, the effects of sintering temperature and composition ratio on the quasi-static reaction of Al/PTFE were ascertained. Wu et al 21 studied the inuence of Al particle size on mechanical properties of Al/PTFE composites, the results show that with the increase of Al particle size, the strength of the composites declined monotonously, and the toughness rose rstly and subsequently decreased. Ding et al 22 utilized a new energy release testing device to investigate the energy release ability of PTFE/Al/CuO.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that with the increase in Al particle size, the strength and sensitivity of the material decreased and the activation reaction of Al and PTFE became more and more difficult to occur. The formation of circumferential open cracks was a prerequisite for the Al-PTFE specimens to undergo a reactive reaction [ 10 ]. Cai investigated the mechanical properties of Al-W-PTFE materials and found that the addition of W particles could effectively improve the strength of Al-PTFE [ 11 ].…”
Section: Introductionmentioning
confidence: 99%